ANALISIS RANTAI NILAI AGROINDUSTRI MOCAF (MODIFIED CASSAVA FLOUR) DI KABUPATEN WONOGIRI (Program Studi Agribisnis Fakultas Pertanian Universitas Baturaja, 2015)
The aims of this reasearch is to determine the value chain of agroindustry of modified cassava flour (mocaf) in Wonogiri, to mapping the actors in the value chain, to analyze activities in the value chain of agroindustry of mocaf, and to know the distribution of benefits for actors in the value chain. Selection of research location is done on purpose,this research is located in Wonogiri conducted during the harvest season of cassava from August until October 2014.The study was conducted with a purposive method with the entry point is the midstream segment (agroindustry of mocaf) then do a search with a snowball system to get a sample at the point before and after.The results of this reasearch shows there are four kinds of patterns that are relatively equal value chain and often used by each agroindustry, with the main performers determining in the mocaf value chain are suppliers of raw materials (farmers), processing of mocaf, and marketing actors of mocaf consisting of wholesalers and retailers. In each pattern value chain, the role of farmers still do not get high profits when compared with other actors. The use of chain-type pattern 1, pattern 2, and pattern 4 will expand the marketing and increase demand mocaf, while the use of pattern 3 will maximize profits on mocaf agro-industry.